FATHERLESSNESS AND QUR’ANIC SOLUTIONS IN INDONESIAN MUSLIM FAMILIES BASED ON AL-MĪZĀN BY ṬABĀṬABĀ’Ī’ - Muhammad Shodiq; Abdullah Abdul Kadir; Hasyim Adnani; Arini Alfa Rohmatika (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
Indonesia, as the world’s largest Muslim-majority country, is facing a growing crisis of fatherlessness, with 2,999,577 children reported to have lost access to the functional role of a father in their development (BPS, 2021). Previous studies in Indonesia have largely examined fatherlessness from psychological, sociological, or normative perspectives, focusing on its impacts or offering general Islamic moral guidance. However, there remains a lack of a philosophically grounded, Qur’an-based framework that conceptualizes fatherlessness as a functional crisis while providing a systematic and prescriptive solution rooted in classical exegesis. Addressing this gap, this study critically examines the philosophical and normative foundations of the father’s role through the socio-philosophical interpretation of Allāmah Muhammad Husain Ṭabāṭabā’ī in Al-Mīzān fī Tafsīr al-Qur’ān. Employing qualitative thematic exegesis (tafsīr al-mawḍū‘ī) with a socio-philosophical approach, the analysis focuses on QS. al-Baqarah: 233, QS. al-Isrā’: 24, and QS. at-Taḥrīm: 6. The findings reveal that fatherlessness should be understood not as biological absence, but as functional absence (mafhūm), reflected in the erosion of paternal responsibilities. Ṭabāṭabā’ī conceptualizes fatherhood as an expression of qawwāmah grounded in fitrah and functional justice, manifested in three inseparable pillars: provider, protector and source of affection, and moral leader. The study contributes by formulating the Three Pillars of the Father’s Role model, offering a holistic framework to address the psychosocial and moral consequences of fatherlessness in contemporary Indonesian Muslim families.